A non‐pollinating moth inflicts higher seed predation than two co‐pollinators in an obligate pollination mutualism. (27th May 2019) - Finch, Jonathan T. D.; Power, Sally A.; Welbergen, Justin A.; Cook, James M.
Abstract : 1. Mutualisms are relationships of mutual exploitation, in which interacting species receive a net benefit from their association. In obligate pollination mutualisms (OPMs), female pollinators move pollen between the flowers of a single plant species and oviposit eggs within the female flowers that they visit. 2. Competition between co‐occurring pollinator species is predicted to increase pollinator virulence, i.e. laying more eggs or consuming more seeds per fruit. Plants involved in OPMs frequently host various non‐pollinating seed parasites and parasitoids that may influence the outcome of the mutualism. Quantifying the prevalence of parasites and parasitoids and competition between pollinators is important for understanding the factors that influence OPM evolutionary stability. 3. This study investigated the pollination mutualism occurring between the leaf flower plant, Breynia oblongifolia, and its co‐pollinating Epicephala moths. A third moth, Herpystis, also occurs in B. oblongifolia fruits as a non‐pollinating seed parasite. 4. Breynia oblongifolia fruits were collected to quantify seed predation and compare seed predation costs between the three moth species. Results showed that the larvae of the two pollinator species consume similar numbers of seeds, and that adults deposit similar numbers of eggs per flower. As such, no evidence of increases in virulent behaviours was detected as a result of competition between co‐pollinators. 5. By contrast, the seed parasite Herpystis consumed more seeds than either pollinator species, and fruit crops with a high proportion of Herpystis had significantly lower net seed production. 6. This work adds to the growing understanding of the ecology and dynamics of plant–pollinator mutualisms. Abstract : Plants involved in obligate pollination mutualisms frequently host various non‐pollinating parasites and parasitoid wasps. Competition between co‐occurring pollinator species is predicted to increase pollinator virulence, i.e. laying more eggs. No evidence was detected of increases in virulent behaviours as a result of competition. Pollinator species consumed similar numbers of seeds and deposited similar numbers of eggs per flower. By contrast, the seed parasite Herpystis consumed more seeds than either pollinator species, and fruit crops with a high proportion of Herpystis had significantly lower net seed production.